Statins in depression: a repurposed medical treatment can provide novel insights in mental health - De Giorgi, R; Cowen, PJ; Harmer, CJ (Taylor and Francis Group, 2022)
Depression has a large burden, but the development of new drugs for its treatment has proved difficult. Progresses in neuroscience have highlighted several physiopathological pathways, notably inflammatory and metabolic ones, likely involved in the genesis of depressive symptoms. A novel strategy proposes to repurpose established medical treatments of known safety and to investigate their potential antidepressant activity. Among numerous candidates, growing evidence suggests that statins may have a positive role in the treatment of depressive disorders, although some have raised concerns about possible depressogenic effects of these widely prescribed medications. This narrative review summarises relevant findings from translational studies implicating many interconnected neurobiological and neuropsychological, cardiovascular, endocrine-metabolic, and immunological mechanisms by which statins could influence mood. Also, the most recent clinical investigations on the effects of statins in depression are presented. Overall, the use of statins for the treatment of depressive symptoms cannot be recommended based on the available literature, though this might change as several larger, methodologically robust studies are being conducted. Nevertheless, statins can already be acknowledged as a driver of innovation in mental health, as they provide a novel perspective to the physical health of people with depression and for the development of more precise antidepressant treatments.